In an other's moves : empathy and embodiment in the creating of a syncretic ensemble. - Schwartz, Sarah (My University, 2011)
This research project, both the performance Flight and the present written engagement with the work, interrogates how the processes of empathy and embodiment contribute to the creation of a syncretic ensemble which speaks simultaneously to the performers’ individualities and to the communal voice made of those individuals. As Jean-Francois Lyotard observed forty years ago, the age of the Grand Narrative is over; the world has become pluralistic and fractured. Yet the intercultural trend in drama of the 1960s through the 1980s aimed at creating a communion through a universalized ensemble. These ensembles “built” themselves through stripping away cultural markings and individuality paralleling the rise of corporate globalization. This creative research project seeks to shift the method of building ensemble from stripping to genuine construction, thus working from each performer’s individuality to build a harmonious collective voice rather than a uniform one. By using the practice as research paradigm to investigate the process of building ensemble, I, as practitioner-researcher, was able to engage deeply with theory to inform the collaborative production called Flight as well as to commune with the creative gifts of six performers who created the piece with my guidance. We worked from Edmund Husserl and Edith Stein’s construction of empathy, Richard Schechner’s concept of performance, as well as from Paul Ricoeur and others’ understanding of narrative as an expression of identity to develop Flight. Using these ideas as our foundation, each collaborator worked to understand the others’ stories well enough to enhance the representation of the experience with their own interpretation while preserving the integrity of the original. The findings of this research come from the work of creating Flight and from the reflections of myself and the six collaborators. This research traces the development of a unique choreography that functions as a translation of emotion, memory, concept or experience into physical movement. The paper illustrates the ways in which our process of alternating reflection and creation allowed a layering of different interpretations while remaining a cohesive narrative. By fusing our voices through performing each other’s experiences, we found a way to build an ensemble voice that maintained the unique presence of each performer. Regarding the trend of “verbatim theatre” or naturalistic representation, this study finds that a more abstracted approach, such as our “associative choreography,” allows a deeper personal engagement from performers. This translates into profound investment in the narrative and collaboration which in turn creates a layering of different personal interpretations in the performance. Additionally, in analyzing the theatrical performance Flight, this paper finds that by blending and linking different interpretations of the same story together, associative choreography creates a polysemic narrative that evades a singular meaning. In this way syncretism is not only a more realistic representation of the postmodern cultural reality but serves to destabilize the normative narrative.